Research on the Visual Image Design of Wuhan Urban Subway from the Perspective of Semiotics (London Journal of Research In Humanities and Social Sciences, 2026)
As an important part of urban infrastructure, the subway not only meets the needs of transportation, but also undertakes the function of urban cultural communication. Based on the theory of semiotics as the research framework, combined with the space environment of Wuhan subway, from the perspective of visual symbol system, this paper analyzes the role of subway visual image design in shaping urban cultural symbols, enhancing public communication and enriching emotional experience. Through field research and case analysis, this paper combs the visual strategies of Wuhan Metro in the creation of three kinds of spatial atmosphere of art, humanities and science and technology, and summarizes the specific paths of visual language system construction, thematic space shaping and future narrative guidance. The research results show that the symbolic visual design improves the cultural recognition and citizen ‘s sense of belonging of Wuhan Metro, and expands the cultural expression of public space. This paper hopes to provide theoretical support and practical reference from the perspective of semiotics for the construction of visual image of urban rail transit, and help to enhance the cultural soft power of Wuhan
Keywords: semiotics; urban subway; visual image; Wuhan